Oxidative Stress and Space Biology: An Organ-Based Approach - Melpo Christofidou-Solomidou (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Technological advances now allow the planning of deep space exploration missions with the aim to discover new habitats for humankind. The National Aeronautics and Space Administration (NASA) has spearheaded this effort and the research into the identification of risks to crew members associated with such lengthy missions. Exciting work from a multitude of investigators across the US, Europe and Japan have identified oxidative damage as a significant risk to major organs that could pose a threat to the health of the astronauts and the success of the mission. This Special Issue of IJMS is dedicated to providing a comprehensive overview of the identified risks and focus on how oxidative stress specifically could impact major organ systems when exposed to space-relevant conditions such as cosmic/galactic radiation, solar particle events, hypogravity, hyperoxia and hypoxia or a combination of stressors.